Serra Pelada: experiência, memórias e disputas - Moura, Salvador Tavares de (2008)
This paper is proposed to discuss the relations of work and the living conditions of workers in the gold mining camps of Serra Pelada, in southeastern Pará, from the memory of the mining's workers. Thus, from the experiences, we can understand the workers in their relationship with the authorities and with the different workers. This reflection allows questioning the past and confronts the different memories of the mining's workers with each other, and with the authoritarian practices of the military regime in the administration of gold mining camps in the years 1980. In this process, the struggle for land indicates how the memory is an argument and builds the place in the formation of consciousness of the miners through the experience. This perspective indicates an intentional choice to deal directly with sectors that had few opportunities to exhibit their point of view. Thus, the role of narrators and the relationship between them and the researcher becomes the object of reflection, and the evidence shows the complexity of the place where the narratives are legitimate and earn meanings. The intention is the visibility to the struggle of the miners of Sierra Pelada from the plurality of memories, their living conditions and housing of today. The present, thus, turns into the right to the memory, the question of how public politics in relation to miners mix itself in the dispute by hegemony, muting projects and alternative possibilities of building other different histories of which were submitted. It discusses the construction of the images on the gold mining camps and the construction of the Carajás region from different perspectives and interests. Furthermore, a revision in the literature on the subject of gold mining camps in the region. Are addressed the questions about the construction of the work, realizing the formation of the gold mining camps as territory, experience shared by the various citizens involved. Serra Pelada emerges as place where disputes between miners, entrepreneurs, CVRD and military, were marked by tensions and struggles. The experience of the gold mining camps changed the miners, forging in the territory, the emergence and the formation of new social citizens